Pengaruh pendidikan kesehatan senam kaki melalui media audio visual terhadap pengetahuan pelaksanaan senam kaki pada pasien DM tipe 2 - Novelia Wulan Dari; Sofiana - Nurchayati; Oswati - Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purposes of this research was to determine the effect of health education about foot exercise by using audio visual media for increasing knowledge of foot exercise among DM patients type 2. The design of this study was quasy experiment. 30 respondents was taken by purposive sampling method. The instrument used this questionnaire that had been tested for validity & reliability (0,933). The result showed the effect of health to improve knowledge of foot exercises implementation in respondents with type 2 of DM in the experimental group after giving the health education was siqnificant (p value 0.002 <α 0.05). The results of this study recommends that the health workers provide health education by using audio-visual media to enhance knowledge of the diabetic patient to do foot exercise and prevent the occurrence of complications of diabetic, especially in the legs. Keywords : audio visual media, foot exercises, health education, knowledge References : 62 (2004-2013)